Fabrication and anti-microbial evaluation of drug loaded polylactide space filler intended for ridge preservation following tooth extraction - Nebu George Thomas; George P Sanil; Gopimohan Rajmohan; Jayachandran V Prabhakaran; Amulya K Panda (Wolters Kluwer Medknow Publications, 2011)
Background: The preservation or reduction of alveolar ridge resorption following tooth extraction is important in patients especially for those intended for implants at a later stage. One way to achieve this is by using membranes, graft materials, and biodegradable space fillers to prevent alveolar bone resorption and promote regeneration. A major attraction for using biodegradable and biocompatible polymers as space fillers for ridge preservation is their safety profile in comparison to xenograft materials like lyophilized bone and collagen. Materials and Methods: Biocompatible polylactide space fillers were fabricated by fusing porous polylactide particles. The sponges were loaded with drugs by placing them in the respective solutions. Pseudomonas aeruginosa was isolated from a chronic periodontitis patient and in vitro anti-microbial evaluation was done with the drug loaded sponges. Results: Chlorhexidine loaded space filler showed significant anti microbial effect against multiple drug resistant Pseudomonas aeruginosa isolated from a patient with chronic periodontitis. Conclusion: The results of this study indicate that biodegradable drug releasing polylactide space fillers has the potential to be used for ridge preservation following tooth extraction. Release of drugs in the socket may prove useful in preventing development of alveolar osteitis post extraction which can interfere with normal healing of the socket. Synthetic biodegradable polymers also exhibit a controlled degradation rate to achieve complete resorption within the intended time.